PENGARUH IMPLEMENTASI STRATEGI PEMASARAN HIJAU DAN KARAKTERISTIK KONSUMEN TERHADAP PILIHAN PRODUK (Studi Empiris Pada Konsumen AMDK Di Surakarta) - Wiyadi Wiyadi (Benefit: Jurnal Manajemen dan Bisnis, 2015)
This study aimed to analyze the effect of an implementation of green marketing strategies and consumer characteristics on product choice decision. Implementation of green marketing strategies such as: product, price, promotion, and distribution channel. The characteristics of consumer such as: consumer awareness, and gender. The research sample is 100 AMDK consumers in Surakarta taken by using purposive sampling technique. Many variables measured by using a Likert scale, exception for variable of gender and product choice decision. To determine the effect of product, price, promotion, distribution channel, consumer awareness, and gender variables on products choice decision used logistic regression analysis. Based on data analysis, product (B = 2,489), price (B = -3,278), and distribution (B = 2,882), and gender (B = -4161) significantly effect on AMDK product choice decision. While the promotion (B = -0,313) and consumer awareness (B = 1,861) not significantly effect on AMDK product choice decision.